KEAKURATAN UMPAN BALIK ASESMEN TERHADAP HASIL BELAJAR KOGNITIF SISWA PADA PENGERJAAN FORMATIF SECARA DARING - Shiela Gunawan; Robert Harry Soesanto (Universitas Muria Kudus, 2022)
The purpose of this study is to discuss the accuracy of feedback assessments on student learning outcomes cognitively, especially in carrying out formative tests during online learning.The research method used is descriptive qualitative. The research was conducted for 8 weeks at a private junior high school located in the city of Tangerang, in the July-August 2021 range. The research instruments used were observation and documentation sheets which had been validated by 3 lecturers who handled the field experience program being carried out. At the observation stage, it is shown how the teacher provides feedback on students' formative tests. From the results of these observations, the researcher then carried out formative tests and provided feedback which was arranged in detail according to the mistakes made by each student. After that, researchers compared it to student learning outcomes. Furthermore, it is documented and presented in the form of pictures.The results of the study found that providing accurate feedback is very important to improve learning outcomes, especially the cognitive domain of students in working on formative tests. This is reflected in the accuracy of providing student assessment feedback through the work of student formative tests. Through this research, students' cognitive learning outcomes can be increased by providing teacher feedback. The conclusion of this study is that teachers need to consider the quality of the descriptive words used in providing feedback.